A Diamond Approach to Develop Virtual Object Interaction: Fusing Augmented Reality and Kinesthetic Haptics - Alma Rodriguez-Ramirez; Osslan Osiris Vergara Villegas; Manuel Nandayapa; Francesco Garcia-Luna; María Cristina Guevara Neri (Multimodal Technologies and Interaction)
Using the senses is essential to interacting with objects in real-world environments. However, not all the senses are available when interacting with virtual objects in virtual environments. This paper presents a diamond methodology to fuse two technologies to represent the senses of sight and touch when interacting with a virtual object. The sense of sight is represented through augmented reality, and the sense of touch is represented through kinesthetic haptics. The diamond methodology is centered on the user experience and comprises five general stages: (i) experience design, (ii) sensory representation, (iii) development, (iv) display, and (v) fusion. The first stage is the expected, proposed, or needed user experience. Then, each technology takes its homologous activities from the second to the fourth stage, diverging from each other along their development. Finally, the technologies converge to the fifth stage for fusion in the user experience. The diamond methodology was tested by generating a user’s dual sensation when interacting with the elasticity of a tension virtual spring. The user can simultaneously perceive the visual and tactile change of the virtual spring during the interaction, representing the object’s deformation. The experimental results demonstrated that an interactive experience can be felt and seen in augmented reality following the diamond methodology.